Legal Writing - Campbell, I D (Victoria University of Wellington Law Review, 1999)
This issue of the Victoria University of Wellington Law Review provides an opportunity for students to develop their skill in written analysis and argument. In turn, the author uses this issue as an opportunity to consider the standards by which a writer should be guided both in their own creative work and in assessing the work of others by using Professor W Friedmann’s Law and Social Change in Contemporary Britain as a framework. According to the author, legal writing requires absolute integrity to the facts, full candour as to the facts, avoiding distortion and straw-men targets in arguments, consistency, and clarity and accuracy.